Gathering blue A Companion To The Newberry Award Winner The Giver - LOWRY, LOIS; LOIS LOWRY (New York dell Laurel-Leaf, 2000)
a dystopian novel about Kira, a disabled, orphaned girl in a harsh society that abandons the weak.
Keywords: post-apocalyptic society that abandons the weak and disabled; resilience, the power of art, and the importance of compassion in a society that often favors selfishness